Tārikh-i ravābit-i Īrān va Nāpuli'ūn - ʻAbbās Mīrzā, Iʻtiz̤ād al-Dawlah (Intishārāt-i Zarrīn, 1984)
On diplomatic relations between Napoleon I, Emperor of the French. 1769-1821, and Iran; includes a supplement on the British and Russian Foreign policies towards Iran.